2021
DOI: 10.1523/jneurosci.2829-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

HDAC3 Activity within the Nucleus Accumbens Regulates Cocaine-Induced Plasticity and Behavior in a Cell-Type-Specific Manner

Abstract: Epigenetic mechanisms regulate processes of neuroplasticity critical to cocaine-induced behaviors. This includes the Class I histone deacetylase (HDAC) HDAC3, known to act as a negative regulator of cocaine-associated memory formation within the nucleus accumbens (NAc). Despite this, it remains unknown how cocaine alters HDAC3-dependent mechanisms. Here, we profiled HDAC3 expression and activity in total NAc mouse tissue following cocaine exposure. Although chronic cocaine did not affect expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…Brain-specific HDAC4 knockout in mice impaired hippocampus-dependent memory and long-term synaptic plasticity [112]. Chronic cocaine-induced promoter-specific change in HDAC3, which is known as a negative regulator of memory formation, in the NAc and interfering HDAC3 activity restored cocaine-induced synaptic plasticity [113]. In addition, SIRT1 knockout mice also exhibited impaired memory and hippocampal plasticity [72].…”
Section: Hdac and Neuronal Plasticitymentioning
confidence: 99%
“…Brain-specific HDAC4 knockout in mice impaired hippocampus-dependent memory and long-term synaptic plasticity [112]. Chronic cocaine-induced promoter-specific change in HDAC3, which is known as a negative regulator of memory formation, in the NAc and interfering HDAC3 activity restored cocaine-induced synaptic plasticity [113]. In addition, SIRT1 knockout mice also exhibited impaired memory and hippocampal plasticity [72].…”
Section: Hdac and Neuronal Plasticitymentioning
confidence: 99%
“…Acetylation and deacetylation of chromatin is another signaling pathway involved in regulating the formation of drug context-associated memories contributing to addiction-like behaviors (Rogge et al, 2013;Bender and Torregrossa, 2020;Campbell et al, 2021). These processes are regulated by two kinds of functionally similar enzymes.…”
Section: Function Of Epigenetic Mechanisms In Preventing Drug Relapsementioning
confidence: 99%
“…In addition, it is important to emphasize that gene-regulatory processes may include multifaceted epigenetic regulations such as histone modifications associated with DNA methylation. Interestingly, a recent study demonstrated that disrupting HDAC3 histone deacetylase activity altered target-specific changes in gene expression and synaptic plasticity in the NAc following cocaine exposure, but had no effect on behavioral responses to cocaine [110]. This provides further evidence for the complexity of epigenetic mechanisms driving cocaine-related behaviors, and emphasize the difficulty of establishing causal relationships with a single set of experiments.…”
Section: Future Studiesmentioning
confidence: 94%